Family monetary incentives as a value‐based care model for oral hygiene: rationale and design of the BEhavioral EConomics for Oral health iNnovation (BEECON) trial. (8th October 2020) - Ramos‐Gomez, Francisco; White, Justin S.; Lindau, Helen E.; Lin, Tracy K.; Finlayson, Tracy L.; Liu, Jenny X.; Gansky, Stuart A.
Abstract: Background: Effective prevention‐focused, value‐based strategies are needed to improve oral health. Despite evidence that monetary incentives can motivate healthy behavior, well‐powered studies have yet to examine incentives for improving children's oral hygiene. Aim: Describe the rationale and design of the BEhavioral EConomics for Oral health iNnovation (BEECON) trial, which tests lottery‐based monetary incentives as a consumer‐oriented, value‐based care model for improving children's oral hygiene. Design: Phase II, stratified, permuted block randomized, controlled, two‐arm, parallel groups, prevention trial. Setting: Study visits occur at three Los Angeles, CA health clinics. Participants: Two hundred and forty‐four parent‐child dyads with a child aged 6‐48 months. Interventions: Eligible dyads were randomized in equal allocation to one of two groups: lottery incentive group or waitlist (delayed incentive) control group. Weekly lottery incentives were offered for 6 months based on Bluetooth‐recorded toothbrushing frequency. Both groups received weekly text message feedback on toothbrushing performance. Outcomes: The primary outcome was toothbrushing performance from baseline to 6 months, measured as the mean number of qualifying half‐day Bluetooth‐recorded episodes per week when the child's teeth were brushed. Secondary outcomes included toothbrushing performance sustainability through 12 months and dental caries status. Conclusions: BEECON offers a consumer‐oriented approach to promoting value‐based oral health care. We hypothesize that lottery‐based incentives can improve oral hygiene in young children. Study results will inform programming efforts to enhance oral disease prevention in young children. Trial Registration: ClinicalTrials.gov identifier NCT03576326.